A Case Study of Teacher’s Practice and Students’ Preferences of Corrective Feedback in English Speaking Activities in The Classroom - Oktavani, Sheila; Yanto, Elih Sutisna; Miftakh, Fauzi (FKIP-Universitas Riau, 2024)
Corrective feedback as a strategy in teaching and learning speaking skills in English as a Foreign Lanugage (EFL) has become a topic of interest in educational research. Although there are numerous studies on corrective feedback in speaking activities, there is still a limited amount of research involving Indonesian junior high school students as participants and using a qualitative descriptive case study. This study is aims to examine the teacher practice and student preferences regarding the use of corrective feedback in classroom speaking activities with 7th grade students of Karawang Junior High School as participants. The study used a descriptive case study with a qualitative approach. The data collection technique consisted of observation and interview. Data were analyzed using Miles and Huberman’s (1984) interactive model. The findings revealed that the students had a positive attitude towards corrective feedback and recognized its benefits in improving their pronunciation and vocabulary. They prefer immediate responses in challenging circumstances and are satisfied with the amount of feedback they have received. This has the potential to improve EFL teaching practice by allowing teachers to reasses their teaching, particularly in terms of speaking skills, to improve EFL students’ speaking skills.